The Urgency of Facilities and Infrastructure in Improving the Quality of High School Education - Muhammad Adip Fanani (Yayasan Insan Mulia Bima, 2023)
Education is a conscious and planned effort to realize planned and programmed learning, with the aim of developing all the potential of students. Facilities and infrastructure in educational institutions are tools or facilities that have an important role in supporting the success of the educational process in schools. Having adequate facilities directly makes it easier to implement well-planned learning programs. Educational institutions at the high school level must have supporting facilities so that all their potential can be developed. This article uses the type of library research. The data used in this research comes from library sources, documents, journals and articles according to the theme discussed. In this article we will discuss the extent of the urgency of Facilities and Infrastructure to improve the quality of high school level education. Starting from the needs and standards of educational facilities, the role of government and society in accommodating them, and the role of facilities and infrastructure in supporting the quality of education. The hypothesis in this research is that educational institutions ideally have adequate facilities and infrastructure, so that the learning process can run effectively. Regional governments must carry out equal distribution and monitoring in providing assistance so that regional schools can have facilities according to school needs, in an effort to improve students' abilities and achievements in the learning process.